Cross-National Comparison of Twitter Use between South Korea and Japan: An Exploratory Study - Cho, Seong Eun; Park, Han Woo (International JOURNAL OF CONTENTS, 2012)
This study compared cross-national Twitter use between Korea and Japan. The main exploratory variables were a) cultural traits and b) disclosure of geographic information. Twitter use was measured by the degree of reciprocity and the numbers of Tweets, followings, and followers. Data were collected using API-based software and analyzed with independent samples t-tests. Content analysis was conducted to validate the findings. The results indicate that Korean and Japanese users employ their own communication strategies reflecting their cultural orientation. KCI Citation Count: 4